Pengaruh Variasi Kadar Aspal Terhadap Nilai Uji Marshall, Cantabro Loss, dan Asphalt Flow Down - Darmawan, Moch Andre; Rizkiardi, Aditya; Hartatik, Nurani; Prasetyo, Yudi Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Plastic waste has become an urgent global issue. The volume of plastic waste increases every year, making Indonesia one of the world’s largest contributors to plastic waste. On the other hand, Indonesia faces challenges with highway pavement that is affected by weather conditions such as rainfall, as well as vehicle loads. This study aims to analyze the effect of asphalt content on porous asphalt mixtures. The method used in this study was trial and error, beginning with testing of materials including aggregates, PG 70 asphalt, and fillers, all in accordance with the 2018 Revision 2 specifications of the Ministry of Public Works and Public Housing. The study continued with an evaluation of the Marshall stability, Cantabro loss, and asphalt flow-down parameters with asphalt content variations of 4%, 4.5%, 5%, 5.5%, and 6%. The results showed that all percentages met the requirements (>500 kg), with the 6% asphalt content exhibiting the highest Marshall stability value. The Cantabro loss results met the requirements (<35%) at asphalt contents of 4.5%–6%. Meanwhile, the AFD met the requirements (<0.3%) at all percentages; however, as the asphalt content increased, the AFD value also increased.